Source and degradation of plastic debris in the marine environment: A new approach based on carbonyl index and stable isotopes - Pietro Cocozza; Eduardo Di Marcantonio; Claudia Pelosi; Fabrizio Monaci; Massimo Marchesi; Silvia Serranti (Journal of Hazardous Materials, 2026)

Towards resilient forest establishment in Europe: functional traits, genetic diversity and multifunctional design - Anastazija Dimitrova; Marcin Klisz; Enrique Andivia; Claudia Cocozza; Dušan Gömöry; Branko Kanjevac; Mathieu Lévesque; Barbara Mariotti; Jelena Milovanović; Andrea Piotti; Radosław Puchałka; Roberto Tognetti; et al. (New Forests, 2026)
Forest restoration and afforestation across Europe are accelerating, yet the decision-making processes governing forest establishment remain unevenly examined, especially from a biodiversity perspective. Considering this and the global environmental changes of climate shifts, land-use transitions, and biological invasions, the present review provides guidance for planning and establishment of multifunctional forests that enhance biodiversity outcomes without compromising long-term forest productivity or resilience. Aiming to assist both practitioners and researchers, we have particularly focused on tree species selection, plant production and management of forest reproductive material, and on-field establishment practices. Literature revision and expert observations indicate that tree species selection must integrate functional traits, provenance performance, and ecological impact assessments alongside species distribution models, since climatic suitability alone does not predict performance under future conditions. Genetic diversity remains severely underutilized in operational forestry but can be advanced through assisted migration, provenance mixing, and traceable seed sources as practices that need to be better supported and monitored. Concurrently, the plant production chain contains multiple points where genetic diversity is eroded, along with advancement opportunities explored through pan-European projects focusing on diversity standards, regional seed-exchange networks, and low-cost molecular monitoring. On-field, the choice between direct seeding and planting needs to link better genetic diversity targets and site conditions rather than biased preference. And finally, urban forests, increasingly recognized as components of the restoration continuum, require context-specific species selection and a transition from isolated specimen planting to more complex and inclusive design (similar to stand level in natural forests) to deliver meaningful biodiversity and multifunctionality outcomes.

Global Quantitative Review of Container Effects on Nursery Growth and Field Survival in Forest Seedlings - Barbara Mariotti; Enrique Andivia; Pedro Villar-Salvador; Vladan Ivetić; Alessandro Bizzarri; Maurizio Ventura; Roberto Tognetti; Fabio Salbitano; Claudia Cocozza; Alberto Maltoni (Current Forestry Reports, 2026)
Purpose of review Container type, volume, depth, and cultivation density represent key and economically relevant decisions for forest nurseries, as they directly shape seedling traits and outplanting performance. Despite numerous studies, existing knowledge remains fragmented and context-specific, limiting the development of general, evidence-based guidelines. This review examines how these container variables influence seedling morphology in the nursery and outplanting survival across taxonomic plant groups, seedling ages, and planting environments. Recent findings We found that larger container volume and depth increase proportionally more root than shoot growth resulting in reduced shoot-to-root mass ratio (S:R), whereas increasing cultivation density reduces seedling biomass and increases S:R. These patterns are more pronounced in cell containers and in ≤ 1 year-old seedlings. Container depth enhances root development particularly in angiosperms. Larger volume and deeper containers improve outplanting survival, especially in cell containers, in ≤ 1 year-old plants, angiosperms, and in harsher, forest planting sites. Planting site aridity does not modulate the effects of container properties on survival. Interestingly, outplanting survival is influenced by both direct effects of container characteristics and indirect pathways mediated by morphology, which differ between angiosperms and gymnosperms. Summary Container characteristics are major drivers of seedling morphology in the nursery and early field survival. These findings support prioritizing larger containers and cell containers for ≤ 1 year-old stock to optimize performance under harsh planting sites. Increasing container depth promotes larger seedlings by enhancing root growth in large-seeded, taproot-forming angiosperms, whereas survival in gymnosperms appears to be more influenced by cultivation density. This review provides a quantitative basis for improving container selection and nursery decision-making in forest plantings.

Drivers of seedling emergence and early growth of 12 European oak species: Results from a cross-continental experiment - Alexandro B. Leverkus; María Medina; Alba Lázaro-González; Laura Levy; Olivia Lorente-Casalini; Marino P. Reyes Martín; Enrique Andivia; Alessandro Bizzarri; Henrik Böhlenius; Vito E. Cambria; Claudia Cocozza; Branislav Cvjetković; et al. (Forest Ecology and Management, 2026)

Tree ring width and isotope ratios show that high temperatures exceed pollution effects on urban trees: evidence in Pinus pinea in Firenze and Pisa, Central Italy - Lucia Mondanelli; Paolo Cherubini; Fabio Salbitano; Matthias Saurer; Lukas Wacker; Claudia Cocozza (Environmental Science and Pollution Research, 2025)
Urban areas typically experience higher temperatures and reduced precipitation compared to periurban environments, conditions that may strongly influence tree performance. To assess these effects, we studied Pinus pinea in Firenze and Pisa, integrating dendroecological and stable isotope analyses. Ring-width index data did not reveal significant differences in radial growth between urban and periurban trees, suggesting that growth responses alone may underestimate urban stress. In contrast, isotopic analyses provided clearer evidence: δ 13 C and δ 18 O values indicated marked water stress in urban trees, particularly in Firenze, while δ 15 N and F 14 C suggested minimal incorporation of traffic-derived nitrogen or fossil CO 2 , likely due to the protective role of urban parks. These findings highlight an apparent discrepancy, where tree growth suggests resilience, while physiological signals reveal stress linked to urban microclimates. This emphasizes the value of combining multiple indicators to capture tree responses in complex environments. Overall, our results suggest that urban climate exerts a stronger influence on P. pinea than localized traffic emissions, with implications for tree vitality and ecosystem services. Species selection for urban forestry should therefore account for microclimatic constraints to ensure long-term tree performance under ongoing urbanization and climate change.

Coupling remote sensing data and local meteorological measurements to predict thermal stress and its potential mitigation by urban forests - Lucia Mondanelli; Saverio Francini; Livia Passarino; Fabio Salbitano; Andrew Speak; Gherardo Chirici; Claudia Cocozza (Urban Forestry & Urban Greening, 2025)

Mediterranean pine forests: Comparison of fluxes and tree rings of Pinus pinaster Aiton and Pinus pinea L - Nicola Arriga; Matteo Campioli; Mara Bernardi; Andrea Cerasa; Josep Peñuelas; Michele Brunetti; Claudia Cocozza; Alessandro Dell’Acqua; Ernest N. Koffi; Ignacio Goded; Giovanni Manca; Marco Matteucci; et al. (Agricultural and Forest Meteorology, 2025)

Assessing olive tree (Olea europaea L.) responses to water shortage through radio frequency sensors - Valeria Lazzoni; Claudia Cocozza; Danilo Brizi; Marco Moriondo; Cristiana Giordano; Giovanni Argenti; Angelica Masi; Nicolina Staglianò; Marco Bindi; Alberto Maltoni; Monica Anichini; Camilla Dibari; et al. (Computers and Electronics in Agriculture, 2025)

Die-hard seedlings. A global meta-analysis on the factors determining the effectiveness of drought hardening on growth and survival of forest plantations - Jaime Puértolas; Pedro Villar-Salvador; Enrique Andivia; Ishita Ahuja; Claudia Cocozza; Branislav Cvjetković; Jovana Devetaković; Julio J. Diez; Inger S. Fløistad; Petros Ganatsas; Barbara Mariotti; Marianthi Tsakaldimi; et al. (Forest Ecology and Management, 2024)

Potential of Castanea sativa for biomonitoring As, Hg, Pb, and Tl: A focus on their distribution in plant tissues from a former mining district - Silvia Traversari; Claudia Cocozza; Francesca Vannucchi; Irene Rosellini; Manuele Scatena; Francesca Bretzel; Eliana Tassi; Andrea Scartazza; Simone Vezzoni (Science of The Total Environment, 2024)

Riparian trees in mercury contaminated riverbanks: An important resource for sustainable remediation management - Guia Morelli; Francesco Ciani; Claudia Cocozza; Pilario Costagliola; Cesare Fagotti; Rossella Friani; Pierfranco Lattanzi; Rosarosa Manca; Alessio Monnanni; Alessia Nannoni; Valentina Rimondi (Environmental Research, 2024)

Integration of ecological indicators to assess a multitemporal impact of cement industries - Claudia Cocozza; Francesco Parisi; Massimo Chiari; Stefano Loppi; Silvana Munzi; Sonia Ravera (Environmental Science and Pollution Research, 2024)
The present study evaluated an integrated biomonitoring approach based on three different bioindicators: tree rings, lichens, and beetles in a complex environment (urban-industrial-forest). In Central Italy, four sampling sites were selected to assess the anthropogenic impact of cement plants taking into account (1) long-term exposure (1988–2020) through the analysis of trace elements in tree rings of Quercus pubescens ; (2) medium-term exposure (2020–2021) through the analysis of trace elements in thalli (outermost portions) of the lichen Xanthoria parietina ; (3) short-term exposure in spring 2021 through the bioaccumulation and evaluation of sample vitality in transplants of the lichen Evernia prunastri and a periodic survey of entomological biodiversity carried out during spring and summer 2021. Trace elements of industrial origin were found in tree rings, with different levels of accumulation between 1988 and 2020 and a maximum in 2012. Native thalli of the lichen X. parietina showed an overall low bioaccumulation of trace elements except for Cr, probably reflecting the influence of national lockdown measures. The transplants of E. prunastri showed a weak stress response in the industrial and urban sites, but not in the forest, and identified Tl and V as the main elements contributing to atmospheric contamination, with peaks at the industrial sites. Concerning the beetles, a significantly lower number of species was found at the Semonte industrial site.

A Global Review on Innovative, Sustainable, and Effective Materials Composing Growing Media for Forest Seedling Production - Barbara Mariotti; Juan A. Oliet; Enrique Andivia; Marianthi Tsakaldimi; Pedro Villar-Salvador; Vladan Ivetić; Antonio Montagnoli; Ivona Kerkez Janković; Nebi Bilir; Henrik Bohlenius; Branislav Cvjetković; Kārlis Dūmiņš; et al. (Current Forestry Reports, 2023)
Purpose of Review The demand for forest tree seedlings is increasing globally, and Sphagnum peat moss is widely used as a component of growing media for container plant production. However, peat extraction is environmentally unsustainable. The forest nursery sector needs to switch to more sustainable alternatives to peat. This review aims to identify potential substitutes for peat by reviewing the worldwide literature on alternative materials for growing media in forest nurseries. Recent Findings Most studies on alternative growing media focused on single plant species growing under local conditions, thereby limiting generalizations about the effectiveness of alternative materials for plant production. To our knowledge, no systematic reviews of scientific literature on the effectiveness of new, alternative-to-peat materials for enhancing plant growth and the associated growing media characteristics for the forest nursery sector are currently available. Summary Most of the analyzed case studies focused on angiosperms (73.1%), with the majority of studies coming from tropical seasonal forests/savannas (36.5%), followed by woodlands/shrublands (31.6%), and temperate forests (15.0%) biomes. Compost was the most studied material (19.5%), followed by bark, other organic materials, and manure (9.8, 9.7, and 8.0%, respectively). Green and municipal wastes were the principal sources of compost (> 60%), while agriculture and green wastes were the first sources of other materials (> 90%). Tested materials were dependent on the geographic region. Thus, manure was the most tested material in Africa and South America, tree bark in North America, and compost in Europe, Asia, and Oceania. Alternative materials effectively provided optimal physicochemical characteristics of growing media and enhanced seedling nursery growth when compared with peat-based growing media in more than 60% of the case studies. This review helps to identify research gaps and, most importantly, provides the basis for the future application of alternative growing media materials in forest nursery management worldwide.

A temporal segmentation approach for dendrometers signal-to-noise discrimination - Saverio Francini; Claudia Cocozza; Teemu Hölttä; Anna Lintunen; Teemu Paljakka; Gherardo Chirici; Maria Laura Traversi; Alessio Giovannelli (Computers and Electronics in Agriculture, 2023)

Uptake of different pharmaceuticals in soil and mycorrhizal artichokes from wastewater - Francesco De Mastro; Gennaro Brunetti; Giuseppe De Mastro; Claudia Ruta; Donato Stea; Sapia Murgolo; Cristina De Ceglie; Giuseppe Mascolo; Filomena Sannino; Claudio Cocozza; Andreina Traversa (Environmental Science and Pollution Research, 2022)

Spatial patterns of leaf shape variation in European beech (Fagus sylvatica L.) provenances - Srđan Stojnić; Vincenzo Viscosi; Milena Marković; Mladen Ivanković; Saša Orlović; Roberto Tognetti; Claudia Cocozza; Verica Vasić; Anna Loy (Trees, 2022)

Monitoring air pollution close to a cement plant and in a multi-source industrial area through tree-ring analysis - Claudia Cocozza; Edoardo Alterio; Olivier Bachmann; Marcel Guillong; Tommaso Sitzia; Paolo Cherubini (Environmental Science and Pollution Research, 2021)
Thirty-two trace elements were examined in the tree rings of downy oak to evaluate the pollution levels close to a cement plant isolated in a rural context and an industrial area where multiple sources of air pollution are or were present. Tree cores were collected from trees growing 1 km from both the cement plant and the industrial area that are located 8 km from each other. The analysis of the trace elements was performed on annual tree rings from 1990 to 2016 using laser ablation inductively coupled plasma mass spectrometry. Trace elements Cs, Mg, Mn, S and Zn reflected the emission history of the cement plant. Their values have increased since early 2000s, when the cement plant started its activity. However, the lack of significant trends of pollutants in the tree rings from the industrial area and the possible effect of translocation and volatility of some elements left open questions. The very weak changes of the other trace elements in the period 1990–2016 suggest those elements do not mark any additional effect of the industrial activity on the background pollution. The results confirm that downy oak trees growing close to isolated industrial plants must be considered a pollution forest archive accessible through dendrochemistry.

Cd and Cu accumulation, translocation and tolerance in Populus alba clone (Villafranca) in autotrophic in vitro screening - Morena Marzilli; Patrick Di Santo; Giuseppe Palumbo; Lucia Maiuro; Bruno Paura; Roberto Tognetti; Claudia Cocozza (Environmental Science and Pollution Research, 2018)

Enhancing phytoextraction of Cd by combining poplar (clone “I-214”) with Pseudomonas fluorescens and microbial consortia - Claudia Cocozza; Domenico Vitullo; Giuseppe Lima; Lucia Maiuro; Marco Marchetti; Roberto Tognetti (Environmental Science and Pollution Research, 2014)

Do tree-ring traits reflect different water deficit responses in young poplar clones (Populus × canadensis Mönch ‘I-214’ and P. deltoides ‘Dvina’)? - Claudia Cocozza; Alessio Giovannelli; Maria Laura Traversi; Gaetano Castro; Paolo Cherubini; Roberto Tognetti (Trees, 2011)